Socio-Economic Impacts of Crisis Management: A Focus on Lockdown and Remote Work Effectiveness During the COVID-19 Pandemic - Damola Victor Akinwande; Georgios Boustras; Omoye Mary Akhagba; Chizubem Benson (Merits)
During the COVID-19 pandemic, lockdown and working from home (WFH) were two significant non-pharmaceutical interventions (NPIs) deployed to stop the spread of the virus and also maintain economic activity. Lockdown caused significant socio-economic disruptions and varied in efficacy by location, even while it helped slow the spread of the virus and provided medical personnel with more time to respond to the crisis. WFH, however, was introduced to mitigate business collapse, and it presented crucial benefits such as flexibility and reduced commuting. However, it also presented major challenges, including work–life conflicts, productivity concerns, and mental health issues. By examining the short- and long-term effects of these NPIs on various sectors and demographics, this study assesses their efficacy in crisis management, and our results show that although WFH and lockdowns were essential for crisis management, their effectiveness varied depending on sectoral differences, timing, and implementation tactics. Furthermore, the ongoing shift towards hybrid work underscores the need for adaptive policies that balance productivity, mental well-being, and economic sustainability. Moreover, future research should focus on exploring the long-term implications of WFH and hybrid work models in order to ensure better preparedness for future crises and refine existing NPIs for more effective crisis management.